HOW TO DEAL WITH FAILURE IN MEDICAL STUDENTS - Rahmadika Akbar, Resti; Nadira, Nadira; Nasution, Latifah Hanum (Yayasan Nuraini Ibrahim Mandiri, 2024)
A medical student is someone who has studied as a doctor for five and a half years at either a state or private university. The large amount of time spent reading reading materials, the need to understand how to effectively serve the community in terms of health, and expectations from parents cause medical students to have higher levels of stress. How to overcome this requires medical students to carry out self-regulation to reduce stress and frustration and facilitate the implementation of problem solving strategies, aspects which include metacognition, motivation and behavior, the influencing factors are the individual (self), behavior and attitude. environment, and also students need to affirm themselves to overcome psychological phenomena, especially stress, emotional intelligence to motivate medical students, overcome frustration and environmental demands or pressure, aspects of emotional intelligence, self-awareness, influencing factors are internal factors that come from within oneself . oneself and external factors that come from outside such as the environment where a person lives, non-family and interpersonal. Next there is self-efficacy, namely a person's belief in their ability to manage the situation they are experiencing. The aspects contained in self-efficacy include quantities related to the level of difficulty of the task, strength, namely how confident the individual is in using it. to carry out tasks, generality, namely individual self-confidence to complete certain tasks completely and well, factors that influence self-efficacy are changes in behavior and emotional arousal. Keywords: Medical Students, Stress, Stress Factors